2019
DOI: 10.1200/jco.18.01223
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Reduced Risk of Internal Malignancies in Patients With Vitiligo: A Nationwide Population-Based Cohort Study

Abstract: PURPOSE Recent studies indicated that the autoimmunity of vitiligo exerts effects on cells other than melanocytes, which confer reduced risks of both melanoma and nonmelanoma skin cancers in patients with vitiligo. However, the risk of internal malignancy in patients with vitiligo has not been elucidated. PATIENTS AND METHODS We conducted a population-based retrospective cohort study using data from the Korean National Health Insurance claims database obtained from January 2007 to December 2016. All patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 45 publications
3
44
2
Order By: Relevance
“…Considering the types of cancers, an increased risk of hematologic cancer has been repeatedly reported in patients with HZ compared with healthy individuals, and the findings for lymphoma, leukemia, and multiple myeloma in the HZ group in this study were in line with previous studies [7, 11, 13-15]. The fact that hematological tumors seem to be linked with cancer is more likely to be true as there have been previous indications [16, 17]. In addition, the possible explanation for the association between HZ and subsequent hematological malignancies could be that the reactivation of VZV promotes neoplastic transformation by triggering continuous antigenic immune stimulation, resulting in lymphoid malignancies [12-14].…”
Section: Discussionsupporting
confidence: 91%
“…Considering the types of cancers, an increased risk of hematologic cancer has been repeatedly reported in patients with HZ compared with healthy individuals, and the findings for lymphoma, leukemia, and multiple myeloma in the HZ group in this study were in line with previous studies [7, 11, 13-15]. The fact that hematological tumors seem to be linked with cancer is more likely to be true as there have been previous indications [16, 17]. In addition, the possible explanation for the association between HZ and subsequent hematological malignancies could be that the reactivation of VZV promotes neoplastic transformation by triggering continuous antigenic immune stimulation, resulting in lymphoid malignancies [12-14].…”
Section: Discussionsupporting
confidence: 91%
“…This observation suggests that inducing melanocyte death elicits an autoimmune response, possibly due to presentation of neo-antigens. A recent study concluded that patients with vitiligo seem to have systemically heightened immune surveillance, as they tend to have a decreased risk of internal malignancy (Bae et al, 2019). Genome-wide association studies identified many vitiligo-associated genes, which include those critical for antigen presentation (e.g., MHC class I and class II), T-cell development (e.g., CD44, SH2B3), T-cell receptor signaling (e.g., PTPN22, UBASH3A), T-cell activation (e.g., CTLA4, IKZF4, CD80), melanocyte homeostasis and melanogenesis (e.g., TYR,OCA2,MC1R,ASIP), and apoptosis (e.g., RERE,GZMB,CASP7,FASLG,BCL2L11,BCL2L12,SERPINB9,NEK6,BAD) (Jin et al, 2010(Jin et al, , 2012(Jin et al, , 2016.…”
Section: Autoimmune Pathog Ene S Is Of Vitili G Omentioning
confidence: 99%
“…The trauma induces stress that triggers an autoimmune response targeting melanocytes (Le Poole & Luiten, 2008); patients have increased risk of developing other autoimmune diseases, such as type 1 diabetes (T1D; Alkhateeb et al., 2003). Furthermore, vitiligo patients tend to have an increased immune response and have lower risk of developing cancers such as squamous cell carcinomas (Bae et al., 2019; Shrestha et al., 2020).…”
Section: The Upr/isr In Disease Pathologymentioning
confidence: 99%
“…Interestingly, the UPR has been implicated in the pathology of T1D (Shrestha et al., 2020), which occurs with a higher than expected frequency in individuals with vitiligo (Dahir & Thomsen, 2018). It is possible that activation of the UPR/ISR contributes similarly to onset of autoimmunity in comorbidities such as vitiligo and T1D, and conversely that UPR modulation of the immune system reduces the risk of skin cancers, which occur less frequently than expected among individuals with vitiligo (Bae et al., 2019). Additional studies are necessary to investigate these questions.…”
Section: The Upr/isr In Disease Pathologymentioning
confidence: 99%